(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
The paper established a so-called analogue-difference method (ADM) to compute the numerical solutions for boundary value problems of higher-order differential equations, which can be a fundamental method and performs much better than the finite difference method (FDM), even for second-order boundary value problems. Numerical examples and results illustrate the simplicity, efficiency and applicability of the method, which also show that the proposed method has obvious advantages over the methods presented by recent state-of-the-art work for induction motor models.